Size and sex compositions, length-weight relationship, and occurrence of the Brazilian sharpnose shark, Rhizoprionodon lalandii, caught by artisanal fishery from southeastern Brazil - Motta, F. S.; Gadig, OBF; Namora, R. C.; Braga, FMS (Elsevier B.V., 2005)
Although the Brazilian sharpnose shark, Rhizoprionodon lalandii (Muller and Henle, 1839), is an inshore species widely distributed in the Western Atlantic from Panama to Uruguay, there is little available information on its biology. During a long-term study of small coastal sharks caught by gill net fisheries in southeastern Brazil (PROJETO CACAO), 3643 specimens of R. lalandii were examined, comprising 61.3% of the total sharks,and including all sizes classes, from 30 to 78,5 cm TL., and weights from 100 to 2950 g. The length-weight relationships were not significantly different between sexes, Overall sex ratio favoured the males slightly at the rate of 1.3: 1. Sex ratios, however, did differ significantly between season and size classes. This species occurred in this area all year long. Three seasonal size-class Occurrence patterns were recognized: (1) between October and March, the juveniles were more frequents (2) from April to July, adults were most common, and (3) from August to September, neonates were most numerically abundant. Such patterns we to associated with reproductive tactics that may reduce intra-specific and inter-specific competition with hammerhead shark neonates (Sphyrna lewini). probably result in reduced natural mortality of the offspring during their first few months. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: elasmobranchii; artisanal fishery; population biology; reproductive easeasonality; Rhizoprionodon lalandii